Transgressão do Paradigma da (multi)Seriação como referência para a construção da Escola Pública do Campo - HAGE, Salomão Antônio Mufarrej (2015)
The article analyzes the reality of rural public schools by including their particularities in the broader challenges facing the popular social movements of rural areas. These social movements seek to ensure the right to universal Basic Education with socially relevant quality and affirmative of the sociocultural and territorial diversity that constitute the rural areas in Brazil. It shares the results of studies carried out by the Group of Study and Research in Rural Education in the Amazon - GEPERUAZ, that investigates the reality of rural schools with multigrade classes, considering the paradox between disrepair and precariousness that to a large extent characterize the conditions of existence of these schools and the creative actions taken by teachers and students in school daily life that defy the adverse conditions experienced therein. It indicates references to the transgression of the urban grading teaching paradigm, currently hegemonic in these schools.